PENGARUH PENAMBAHAN PEKTIN DARI KULIT PISANG KAPAS (Musa acuminata Colla) TERHADAP MUTU SELAI LEMBARAN MANGGA HARUMANIS (Mangifera indica L.) - Tuslinah, Lilis; Rahmawati, Sita; Fathurohman, Mochamad (ARGIPA (Arsip Gizi dan Pangan), 2023)
Pectin is a polymer of D-galacturonic acid linked by α-1,4 glycosidic bonds. Pectin is widely used in the pharmaceutical, food, and beverage industries as a gelling agent and stabilizing agent. This study aims to utilize cotton banana skin waste as an alternative source of pectin and determine the levels of pectin added to make the best quality fragrant mango slice jam. Pectin from cotton banana peels was obtained by extraction using HCl solvent with a pH of 2.5 at 100°C for 120 minutes. The yield obtained was 8.67%. The pectin obtained was analyzed to meet the quality requirements for pectin, namely water content 9.85%, ash content 6.73%, equivalent weight 6,460.485 mg, methoxyl content 2.85%, galacturonic content 75.73%, degree of esterification 21.4 % and spectrum analysis Fourier Transform Infrared (FTIR) and the best slice jam product was obtained with the addition of 1.5% pectin. Then the slice jam was analyzed, and the results obtained were 17.55% water content, 84.56% texture analysis, 70% total dissolved solids, and hedonic tests on the organoleptic of slice jam, namely color, aroma, taste, and texture, which, in general, the subject liked fruit slice jam fragrant mango with the addition of 1.5% pectin from cotton banana peels.